How nurses and other health professionals use learning principles in parent education practice: A scoping review of the literature. Issue 3 (March 2020) - Thompson, Deryn; Leach, Matthew; Smith, Colleen; Fereday, Jennifer; May, Esther
Abstract: Background: Health Professionals (HPs) play an important role in supporting parents to care for their children, by facilitating parents' knowledge and skills development through parent education. This is achieved through teaching, whereby planned strategies, based on principles of how people learn, enable learning. Despite Learning Principles being the fundamental tenets of the learning process, how HPs perceive and use Learning Principles in their practice is neglected in the healthcare literature. Objective: To identify, describe and map the existing literature on nurses' and HPs' perceptions and use of Learning Principles in parent education practice. Method: A scoping review was performed using the Joanna Briggs Institute approach. A comprehensive search of 10 databases and the grey literature was undertaken between March and June 2017 to identify pertinent English-language publications. The search was limited to literature published between 1998 and 2017. Following a screening and inclusion criteria eligibility check, 89 articles were selected for inclusion. Results: HPs' perceptions of Learning Principles were diverse, somewhat disorganised, divergent in meaning and implicit. This was until the Dimensions of Learning construct was applied to guide the analyses and mapping. This revealed that HPs, of whom 60.7% were nurses, used Learning Principles in parent education, but only referred to them in the context of Adult Learning. Enablers to HPs using Learning Principles included shared partnerships between parents and HPs, while barriers included parents' health beliefs, psychological issues and organisational assumptions about learning. Evaluation of parents' learning also represented implicit use of Learning Principles by HPs. Conclusion: This scoping review is the first to examine HPs' perceptions and use of Learning Principles within parent education practice. The findings reveal a significant gap in this body of knowledge. The paucity of studies containing any explicit descriptions of Learning Principles strongly supports the need for further exploration and codification of Learning Principles, through qualitative methods, whereby a deeper understanding of what is happening in healthcare practice can be established. Abstract : Pediatrics; Nursing; Health education; Educational psychology; Health professionals; Parent education; Learning principles, Dimensions of learning